Mas golden boutique online travellers store / Hidayah Sulaiman - Sulaiman, Hidayah (2001)
Malaysia has emerged into the world of World Wide Web thus having to obtain every single update through the Internet. People these days demand transactions to be done fast and save. Having to fill in forms and wait for deliveries can cause inconvenience to the customers. Having to write down their credit card number on a piece of order form and through the Internet is also quite unsafe. Malaysian Airlines Golden Boutique Sdn. Bhd. is a wholly owned subsidiary of Malaysian Airlines and a full-fledged independent retailer whose retailing activities extend from ground retailing and in the fliture, virtual shopping on the Internet. The MAS Golden Boutique's website is developed mainly for the international travelers, as these people are the ones who want to keep up with time and usually demands transactions to be done there and then fast and safe. The development of this website also aims to make MAS Golden Boutique a leading world class retailer as it continues to uphold the high standards established and meet customer satisfaction in the air and ground. The methodology used upon developing this website would be the web development steps adapted from the Waterfall Model for system development. Among the services provided through this website would be information retrieval, product transactions and administration site. The website aims to give fast access of current information on Golden Boutique, easy on-line application for the international travelers, provide products ordering services and minimizing customer's dissatisfaction of unavailable items. All in all, the homepage can be considered as a great investment towards promoting MAS Golden Boutique and also gain interest to the viewers especially the international travelers.